2014
DOI: 10.1097/mib.0000000000000150
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin 5-HT7 Receptor Is Critically Involved in Acute and Chronic Inflammation of the Gastrointestinal Tract

Abstract: The 5-HT7R expressed on CD11c/CD86-positive myeloid cells modulates the severity of intestinal inflammation in an acute and chronic colitis and thus represents a potential therapeutic target for the treatment of inflammatory disorders such as CD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
72
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(76 citation statements)
references
References 54 publications
2
72
2
Order By: Relevance
“…Unfortunately, as compelling as this idea seems to be, strong evidence has been advanced for an equally compelling but contrary hypothesis. Both sides of the argument agree that dendritic cells in the intestine express the 5-HT 7 receptor; however, the contrary evidence suggests that the dendritic cell 5-HT 7 receptor is anti-inflammatory, not proinflammatory [94]. A 5-HT 7 antagonist, SB-269970, and the deletion of 5-HT 7 receptors were found to increase the severity of inflammation, and stimulation of the 5-HT 7 receptor exerted anti-inflammatory effects.…”
Section: Serotoninmentioning
confidence: 99%
See 2 more Smart Citations
“…Unfortunately, as compelling as this idea seems to be, strong evidence has been advanced for an equally compelling but contrary hypothesis. Both sides of the argument agree that dendritic cells in the intestine express the 5-HT 7 receptor; however, the contrary evidence suggests that the dendritic cell 5-HT 7 receptor is anti-inflammatory, not proinflammatory [94]. A 5-HT 7 antagonist, SB-269970, and the deletion of 5-HT 7 receptors were found to increase the severity of inflammation, and stimulation of the 5-HT 7 receptor exerted anti-inflammatory effects.…”
Section: Serotoninmentioning
confidence: 99%
“…A 5-HT 7 antagonist, SB-269970, and the deletion of 5-HT 7 receptors were found to increase the severity of inflammation, and stimulation of the 5-HT 7 receptor exerted anti-inflammatory effects. A difference between the studies is that the proinflammatory side [93] employed a dose of SB-269970 that was 2500-fold higher than that utilized by the anti-inflammatory advocates [94]. Conceivably, the higher dose of SB-269970 exerted non-specific effects.…”
Section: Serotoninmentioning
confidence: 99%
See 1 more Smart Citation
“…The mammalian intestinal tract is the largest immune organ in the body and is composed of several different types of cells [29]. 5-HT serves as a link between the gut and immune regulation [30, 31]. This suggests that 5-HT may be involved in the nervous system-mediated regulation of the digestion-immune system interface.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, recent works have shown that 5-HT [5], 5-HT receptors [6] and SERT [7] would play a chief role in the development of IBD. In fact, recent studies have suggested that modifications of the activity of selective serotonin receptors and reuptake transporter in the gut could be effective for controlling IBD activity and associated symptoms [8,9].…”
Section: Introductionmentioning
confidence: 99%